Multiple-Omics Techniques Reveal the Role of Glycerophospholipid Metabolic Pathway in the Response of Saccharomyces cerevisiae Against Hypoxic Stress - Xia, Zhengchao; Zhou, Xuelin; Li, Jingyi; Li, Lei; Ma, Yi; Wu, Yi; Huang, Zhong; Li, Xiaorong; Xu, Pingxiang; Xue, Ming (Frontiers in Microbiology, 2019)
Although the biological processes of organism under hypoxic stress had been elucidated, the whole physiological changes of Saccharomyces cerevisiae (S. cerevisiae) are still unclear. In this work, we investigated the changes of biological process of S. cerevisiae under hypoxia by the methods of transcriptomics, proteomics, metabolomics and bioinformatics. The results showed that the expression of a total of 1017 mRNA in transcriptome, 213 proteins in proteome and 51 metabolites in metabolome had been significantly changed between the hypoxia and normoxia conditions. Moreover, based on the integration of system-omics data, we found that the carbohydrate, amino acids, fatty acid biosynthesis, lipid metabolic pathway and oxidative phosphorylation were significantly changed in hypoxic stress. Among these pathways, the glycerophospholipid metabolic pathway was remarkably up-regulated from the mRNA, protein and metabolites levels under hypoxic stress, and the expression of relevant mRNA was also confirmed by the qPCR. The metabolites of glycerophospholipid pathway such as phosphatidylcholine, phosphatidylethanolamine, phosphoinositide, and phosphatidic acids probably maintained the stability of cell membranes against hypoxic stress to relieve the cell injury, and kept S. cerevisiae survive with energy production. These findings in the hypoxic omics and integrated networks provide very useful information for further exploring the molecular mechanism of hypoxic stress.